Update breast cancer 2022: Part 3 - Early-stage breast cancer = Update Mammakarzinom 2022 : Teil 3 - Brustkrebs in frühen Krankheitsstadien - Fehm, Tanja; Welslau, Manfred; Müller, Volkmar; Lüftner, Diana; Schütz, Florian; Fasching, Peter A.; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Belleville, Erik; Untch, Michael; Thill, Marc; et al. (Geburtshilfe und Frauenheilkunde, 2022)
This review summarizes recent developments in the prevention and treatment of patients with early-stage breast cancer. The individual disease risk for different molecular subtypes was investigated in a large epidemiological study. With regard to treatment, new data are available from long-term follow-up of the Aphinity study, as well as new data on neoadjuvant therapy with atezolizumab in HER2-positive patients. Biomarkers, such as residual cancer burden, were investigated in the context of pembrolizumab therapy. A Genomic Grade Index study in elderly patients is one of a group of studies investigating the use of modern multigene tests to identify patients with an excellent prognosis in whom chemotherapy may be avoided. These and other aspects of the latest developments in the diagnosis and treatment of breast cancer are described in this review.